2020
DOI: 10.21203/rs.3.rs-72367/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-Sectional Associations Between 24-hour Activity Behaviours and Mental Health Indicators in Children and Adolescents: A Compositional Data Analysis

Abstract: Background. The prevalence of mental ill health increases with age through childhood and adolescence and likely impairs mental and physical health in adulthood. Little is known about the combined influence of sleep, sedentary time (ST), and physical activity on youth mental health. This study examined associations between youth 24-hour activity behaviour compositions and mental health indicators, and investigated predicted differences in mental health when time was reallocated between activity behaviours.Metho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…sedentary time or physical activity). While researchers are starting to examine compositional time use in relation to mental wellbeing in children cross-sectionally [49,50], longitudinal data are scarce [51].…”
Section: Discussionmentioning
confidence: 99%
“…sedentary time or physical activity). While researchers are starting to examine compositional time use in relation to mental wellbeing in children cross-sectionally [49,50], longitudinal data are scarce [51].…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, it may not be surprising that we found replacing up to 25 mins of sedentary time with either LPA or MVPA confers negligible benefits for mental health. Although recent cross-sectional studies have shown movement compositions are positively associated with important physical and cognitive developmental outcomes in the early years (Bezerra et al, 2021;Kuzik et al, 2020;Mota et al, 2020), the benefits for mental health and wellbeing may not manifest until children are of school age (Fairclough et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…Recent work using accelerometry has shown that 24-hour movement compositions significantly predict fundamental motor skills (Kuzik et al, 2020;Mota et al, 2020) and cognitive development (Bezerra et al, 2021;Kuzik et al, 2020) in preschool-age children. Although evidence has demonstrated beneficial associations between different intensities of physical activity and indicators of mental health within samples of children and youth between the ages of 6 to 17 years (Carson et al, 2016;Fairclough et al, 2021), the only study to examine these relationships among preschoolage children observed null relationships (Kuzik et al, 2020). Combined with the fact that children at risk for DCD experience higher rates of mental health problems beginning as early as the preschool years (Rodriguez et al, 2019), this dearth of research highlights the need for additional workparticularly among larger and more diverse samplesto better understand whether movement behaviours influence mental health in the early years.…”
mentioning
confidence: 99%
“…Following institutional ethical approval (#SPA-REC-2018-007) written informed parent consent and participant assent were obtained from 382 students from ten primary and two secondary schools in the West Lancashire region of northwest England. From these, 359 students (23 were absent on data collection days) took part in the study between April 2019 and March 2020, as part of a wider project described elsewhere (14).…”
Section: Methodsmentioning
confidence: 99%
“…To obtain activity behaviours, participants wore triaxial accelerometers [ActiGraph GT9X, ActiGraph, Pensacola, FL, USA], set at 100Hz, on the non-dominant wrist for 24h•day −1 over 7 days. Data were processed in R [http://cran.r-project.org] using GGIR [v1.9.0](17), which performed auto-calibration procedures, identi ed non-wear, and converted raw triaxial accelerometer signals into 1 omnidirectional measure of acceleration (Euclidean Norm Minus-One; ENMO) (14,18,19). ENMO values were averaged per 5s epoch over the 7 monitored days to represent average acceleration expressed as milligravitational units (mg).…”
Section: Methodsmentioning
confidence: 99%